2005
DOI: 10.1364/ao.44.003565
|View full text |Cite
|
Sign up to set email alerts
|

Flame temperature and location measurements of sooting premixed Bunsen flames by rainbow schlieren deflectometry

Abstract: Rainbow schlieren deflectometry (RSD) provides a simple and nonintrusive way of determining the temperature field of axisymmetric flames. This technique is specially suited for the detection of large temperature gradients, such as those near the flame location. We explore the feasibility and accuracy of using RSD to obtain the flame location and thermal structure of premixed Bunsen flames for varying fuel types, equivalence ratios, and soot loadings. Uncertainty analysis is also carried out to provide various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Choosing the reference point at some hot location in the flow is a better choice than the cold ambient, [2], and a flame location was shown to produce lower uncertainties [16]. In the present, the reference point at each downstream station was demonstrating, in turn, that locations of high temperature have larger errors than colder regions.…”
Section: Abel Transformmentioning
confidence: 70%
See 1 more Smart Citation
“…Choosing the reference point at some hot location in the flow is a better choice than the cold ambient, [2], and a flame location was shown to produce lower uncertainties [16]. In the present, the reference point at each downstream station was demonstrating, in turn, that locations of high temperature have larger errors than colder regions.…”
Section: Abel Transformmentioning
confidence: 70%
“…Temperature measurements were attempted in isothermal flows [6,14] using rainbow schlieren and it was shown that the temperature rise could be accurately evaluated. Measurements of temperature in flames followed, typically in laminar premixed flames, where composition variations in rich jet flames [4] or spherical microgravity flames [15] affected the measured temperature to within a few percent and the derived temperature agreed very well with thermocouple measurements; however, for heavier hydrocarbon fuels extra effort is required to model composition effects [16].…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that optical computerized tomography (OCT) has been widely used in various flow fields, including obtaining three-dimensional (3-D) distributions of density [1,2] and temperature [3,4], due to its stable, real-time, and noncontact characteristics. In addition, after the applicability of moiré tomography in diagnosing arc plasma was studied [5], it was also applied to obtain the temperature and electron number density distributions of a plasma flow field [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, validation of complex chemical-kinetics mechanisms using the traditional zero-and one-dimensional experimental/numerical studies can be performed only partially. Alternatively, one could include more target flames, such as coaxial nonpremixed [14], Bunsen [15], and centerbody flames [16], and validate the mechanisms for predicting flame shapes, lift-off heights, blowout characteristics, temperature and species distributions, etc. Most of these data can be obtained using measurement techniques ranging from inexpensive (direct photographs) to expensive (laser diagnostics) techniques.…”
Section: Introductionmentioning
confidence: 99%